ALPHABET BOX AS A MEDIA FOR LETTER PRONOUNCIATION TO INTRODUCE ENGLISH FOR PRIMARY SCHOOL - Fitrah Yuliawati; Iis Faida (IKIP Siliwangi, 2024)
The aim of this research is to recognize letters by using alphabet box media in a good pronounciation for primary students. This research uses qualitative research. From the results of the analysis stage, in the learning process students cannot differentiate between letters that have almost the same shape, for example